Preparedness of Large Retail Malls to Prevent and Respond to Terrorist Attack, 2004 (United States) - Davis, Robert C. ([Verlag nicht ermittelbar], 2007)
The purpose of this project was to assess the level of security in large indoor shopping malls. The researchers administered surveys to the security directors of the nation's largest indoor retail malls. The researchers sent letters with surveys attached, to 1,372 security directors of enclosed retail malls across the country, which were at least 250,000 square feet in size. A total of 120 completed surveys were returned. The survey instrument was divided into the following nine sections: (1) Hiring Standards, (2) Training, (3) Security Budget, (4) Human Surveillance Strategies, (5) Access Control Plans, (6) Technological Enhancements, (7) Emergency Preparedness Procedures, (8) Relations with the Public Sector, and (9) Opinions about Terrorist Threat.